'Equal pay for work of equal value guidelines', 1988 (1988)
1988 1960-2000 "'Equal pay for work of equal value guidelines', 1988" [EP0037c], 1988 This pamphlet, published by the TUC in 1988 to explain the legal provisions of the Equal Pay Act as amended from 1984, outlines the procedure for taking an 'equal value' case before a tribunal.